Knowledge and Practice of the Use of Eye Make-Up and Its Possible Effect on Ocular Dryness among Females in Saudi University - AlShaghab, Mariyyah; Alhussain, Eman (International Journal of Innovative Research in Medical Science, 2017)
Introduction: Several studies report that use of eye cosmetics can lead to multiple complication such as tarsal conjunctival pigmentation and posterior blepharitis by initial migration of cosmetics product material from the external environment to the lash line. Some of these can be controlled and prevented by increasing level of awareness about safe use of cosmetics. Objective: To assess the level of awareness about using of eye make-up and to identify the possible relationships between ocular dryness and make-up misuse among female medical students in Saudi university. Methods: The results were collected from a questionnaire distributed among females in the medical campus, which includes 23 questions. These questions targeted the demographic data, ocular surface disease index (OSDI) score and their eye cosmetics use practices. Each answer was giving certain points after establishing the recommended practices and calculate the score to determine how well they use eye cosmetics. Less than 12 points defined as good practice. Consequently, we examined each participant by a portable slit lamp to detect the presence of anterior or posterior blepharitis. 178 females that met our study criteria were included in the study (median age 21, interquartile range 18-24 years). Subjects with a medical history of any factor known to cause dry eye symptoms were excluded. Results: 88% of participants have used eye make-up, mascara showed to be the most common product used. Only 20% showed proper use of eye make-up and those got normal OSDI score (<15) compared to those who use it improperly (p=0.022). OSDI scores of eye make-up user were similar to non-user (p=0.948). 19%, 3% and 1% of make-up users were found to have mild meibomian gland dysfunction (MGD), anterior blepharitis and chalazion respectively. Conclusion: The level of awareness in regards to the proper use of eye make-up were found to be fairly low among subjects and that may play a role in the dry eye symptomatology. These results could indicate the need to undergo a larger study that includes the whole nation of Saudi Arabia with other environmental and social factors.